Gender, diversity and sexual and reproductive health rights in central America: An anthropological reflection - Binazzi, Alice (Comparative Cultural Studies: European and Latin American Perspectives, 2024)
In this globalised and transnational contemporary world, it often exists perspectives, which are fragmented in “local” realities. Thematic and phenomena, studied in the field, throughout years, had highlighted the need for adopting a strategy of multi-situated field research (Clifford and Marcus, 2005; Marcus, 1995). This also challenges the exploration of new paths, in terms of links and spaces, to be able following complex cultural phenomena, including those related to gender. In this sense, gender - as a social construction - transversally cuts all thematic and it is cross-country, as gender inequalities can be observed, similarly, in many of the world’s contexts. This work approaches, from an anthropological qualitative perspective and by adopting an intersectional view, the sensitive issue of sexual and reproductive health rights of women and girls, in Central American context, further, analysing the peculiar condition of migrant, indigenous and Afrodescendant girls and women, aiming to shed light on discrimination and violence phenomena affecting them.